(untitled) (Damascus University Journal for the economic and Political sciences, 2023)
Under occupation, Palestinian civil society plays an important role in meeting the basic needs of the Palestinian people to support resistance and accomplish national tasks in defeating the occupation, working to raise the level of popular participation, and supporting poor and marginalized groups. This study aims to identify the role of Palestinian civil society in promoting the political participation of women under Zionist occupation in both the Gaza Strip and the West Bank, in light of inherited social customs and traditions that detract from women’s rights, and the existence of a legislative and legal environment against women that has made their political participation a difficult and complex situation and further complicated their cause and struggle for freedom, equality, Zionist occupation and Palestinian division. Promoting the role of Palestinian women and involving them in political life and decision-making.